Actor's statute analysis, notion of Character and Acting Situation in "El centésimo mono" by Osqui Guzman - Misevich , Valeria (2023)
El centésimo mono by Osqui Guzmán puts theatre, actor and character at stake by enabling the audience's critical eye. The play creates an alternate (and interesting) space within the argentine theatre system in the 21st Century which questions the production and expectation conditions of the theatrical event itself. The Character, a splintered, blurred and hard to grasp entity, is the centrepiece of the play and turns into a guide and direct speaker to the audience. The resources and procedures analysed from a theoretical perspective that appeals not only to its own concepts but also to other fields of cultural thinking, make it possible for a more complex analysis of the actor-character duality and his performance on stage. El centésimo mono is a play where the actorsubject leaves his own marks through the cracks which open up the plot by magic.